I Ideology in Western thought: Diversity of views and multiplicity of definitions - yaiche khizar, Ousila (Al-Adab Journal, 2019)
The term "ideology", which is no more than 200 years old, has preoccupied a large number of researchers and thinkers in various fields of human and social sciences. Although this concept is widely used, there is no consensus on its definition. It is no exaggeration to say that "ideology" is one of the most controversial and least well-defined concepts. Indeed, "ideology", as a social and historical construct, has become a cultural product par excellence, with multiple functions and uses according to the multiplicity of goals and different ideological interests. This paper endeavours to disambiguate the concept of "ideology", by revealing the various meanings that have been accrued to it in Western thought, and by identifying the most prominent points of transformation and modification that it has been subjected to through its historical course. In order to achieve this endeavour, the research has been divided into seven modules. Each module presents one of the definitions of ideology, accompanied with intellectual models that embody this diversity of views and multiplicity of meanings. Keywords: ideology, Ideonomy, false consciousness, class conflict, political ideology, totalitarian ideology.